Moderasi Beragama dalam Perspektif Al-Qur’an dan Hadis - Anwar, Syaeful; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Moderation is a way of looking at a person's view of an event they are facing or currently experiencing. In the midst of modernization today, as pluralistic creatures, we must always have a wise attitude in viewing differences, whether in terms of religion, culture, economics, and so on. Meanwhile, the current democratic system considers that everything must be seen from various perspectives and views that are based on